Genetic and Clinical Predictors of Left Atrial Thrombus: A Single Center Case-Control Study. (28th June 2021) - Springer, Adrian; Schleberger, Ruben; Oyen, Florian; Hoffmann, Boris A.; Willems, Stephan; Meyer, Christian; Langer, Florian; Schnabel, Renate B.; Kirchhof, Paulus; Schneppenheim, Reinhard; Lemoine, Marc D.
Left atrial (LA) thrombus formation is the presumed origin of thromboembolic complications in patients with atrial fibrillation (AF). Beyond clinical risk factors, the factors causing formation of LA thrombi are not well known. In this case-control study, we analyzed clinical characteristics and genetic thrombophilia markers (factor V Leiden (FVL), prothrombin G20210A (FIIV), Tyr2561 variant of von Willebrand factor (VWF-V)) in 42 patients with AF and LA thrombus (LAT) and in 68 control patients with AF without LAT (CTR). Patients with LAT had more clinical conditions predisposing to stroke (mean CHA2 DS2 -VASc-score 3.4 ± 1.5 vs. 1.9 ± 1.4; P < 0.001), a higher LA volume (96 ± 32 vs. 76 ± 21 ml, P = 0.002) and lower LA appendage emptying velocity (0.21 ± 0.11vs. 0.43 ± 0.19 m/s, P < 0.001). Prevalence of FVL, FIIV and VWF-V mutations was not different, but in the subgroup of patients <65 years (y) there was a tendency for a higher incidence of VWF-V with a prevalence of 27% (LAT <65 y) vs. 7% (CTR <65 y, P = 0.066). These findings warrant further investigation of the VWF-V as a risk factor for LA thrombogenesis in younger patients.